Rahnella perminowiae sp. nov., Rahnella bonaserana sp. nov., Rahnella rivi sp. nov. and Rahnella ecdela sp. nov., isolated from diverse environmental sources, and emended description of the genus Rahnella. Issue 1 (20th January 2022) - Brady, Carrie; Asselin, Jo Ann; Beer, Steven; Brurberg, May Bente; Crampton, Bridget; Venter, Stephanus; Arnold, Dawn; Denman, Sandra
Abstract : Bacteria isolated from onion bulbs suffering from bacterial decay in the United States and Norway were previously shown to belong to the genus Rahnella based on partial housekeeping gene sequences and/or fatty acid analysis. However, many strains could not be assigned to any existing Rahnella species. Additionally, strains isolated from creek water and oak as well as a strain with bioremediation properties were assigned to Rahnella based on partial housekeeping gene sequences. The taxonomic status of these 21 strains was investigated using multilocus sequence analysis, whole genome analyses, phenotypic assays and fatty acid analysis. Phylogenetic and phylogenomic analyses separated the strains into five clusters, one of which corresponded to Rahnella aceris . The remaining four clusters could be differentiated both genotypically and phenotypically from each other and existing Rahnella species. Based on these results, we propose the description of four novel species: Rahnella perminowiae sp. nov. (type strain SL6 T =LMG 32257 T =DSM 112609 T ), Rahnella bonaserana sp. nov. (H11b T =LMG 32256 T =DSM 112610 T ), Rahnella rivi sp. nov. (FC061912-K T =LMG 32259 T =DSM 112611 T ) and Rahnella ecdela sp. nov. (FRB 231 T =LMG 32255 T =DSM 112612 T ).